Extending language learning beyond the EFL classroom through WhatsApp. Issue 8 (2nd November 2022) - Tragant, Elsa; Pinyana, Àngels; Mackay, Jessica; Andria, Maria
Abstract: WhatsApp is a powerful tool for L2 learning because of its capacity to promote interaction between teacher and student, as well as among students. Its use has also been shown to support ubiquitous learning. In an attempt to extend language learning beyond the classroom, this study reports on the use of instant messaging through WhatsApp by a group of EFL learners (n = 23) who were regularly sent optional language-learning tasks by their teacher during an intensive summer course. By the end of a five-week-period, 764 messages had been produced, which are explored through a qualitative analysis in the present study, with particular attention to changes of participation as a result of time. Most of the messages in the WhatsApp group were produced by the students in the context of the teacher-initiated tasks and through them students had the chance to practice the language as well as engage in real communication, even though student participation tended to decrease over time. The WhatsApp group was also used for informal communication among the students and with the teacher (a total of 289 off-task messages) which, in contrast to on-task messages, grew over time. The nature of the interactions also tended to be more spontaneous and symmetrical, at times with more of a presence of textese. Negotiation of form and content was scarce, but both on-task and off-task messages turned out to be equally productive in engaging students to use English beyond the walls of the classroom.